Increased Bleeding during Liver Resection in Ethanol-Intoxicated Rats - Bengmark, Stig; Göransson, Göran; Idvall, Jan; Zoucas, Evita (Thrombosis and Haemostasis, 1980)
The effect of ethanol intoxication on hemostasis after liver resection was studied in the rat. Plasma levels of ethanol were within the range of those found in ethanol intoxication in man. Bleeding time and blood loss were significantly increased, whereas hemoglobin and hematocrit values were decreased after resection in intoxicated animals compared to controls. APT-times and platelet counts did not differ significantly between the two groups of rats. ADP- and collagen-induced platelet aggregation was slightly inhibited one hour after ethanol administration in non-operated animals. A decrease in pH, such as observed in intoxicated animals, did not affect hemostasis. Distribution of cardiac output was significantly altered after ethanol intoxication. Renal blood flow was increased by 54%, blood flow in the hepatic artery by 40% and in the portal vein by 47%.
Keywords: Ethanol-intoxication; Bleeding time; Blood loss; Platelet aggregation